2013
DOI: 10.1155/2013/489865
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity and Other Factors Affecting Treatment Adherence in Pulmonary Tuberculosis Patients

Abstract: As the overall prevalence of TB remains high among certain population groups, there is growing awareness of psychiatric comorbidity, especially depression and its role in the outcome of the disease. The paper attempts a holistic approach to the effects of psychiatric comorbidity to the natural history of tuberculosis. In order to investigate factors associated with medication nonadherence among patients suffering from tuberculosis, with emphasis on psychopathology as a major barrier to treatment adherence, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
168
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(185 citation statements)
references
References 151 publications
3
168
0
14
Order By: Relevance
“…Psychiatric problems such as depression can significantly affect patient quality of life, as well as physician's approach toward MDR-TB therapy. Consequently, effective management of depression is critical not only for desired patient outcome, but also for patient's overall health and physician's satisfaction while dealing with MDR-TB therapy [16].…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric problems such as depression can significantly affect patient quality of life, as well as physician's approach toward MDR-TB therapy. Consequently, effective management of depression is critical not only for desired patient outcome, but also for patient's overall health and physician's satisfaction while dealing with MDR-TB therapy [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a recent study patients with PT were reported to have higher depression, anxiety, loneliness, stigmatized, and social isolation levels may affect adversely proper antituberculosis treatment compliance. (4)(5)(6) Tuberculosis is known to be a social illness. In addition, tuberculosis is accepted as a stigmatizing disease as well.…”
Section: Introductionmentioning
confidence: 99%
“…Depressed individuals with TB are less likely to seek care promptly, if at all, and once in treatment are significantly less likely to take medications consistently and/or completely (2,4,7). These treatment irregularities can lead to drug resistance, morbidity and mortality.…”
mentioning
confidence: 99%